Minimality and Sylow-Permutability in Locally Finite Groups - Robinson, D.J.S. (Український математичний журнал, 2002)
We give a complete classification of the locally finite groups that are minimal with respect to Sylow-permutability being intransitive. Наведемо повну класифікацію локально скінченних груп, мінімальних із нетранзитивною властивістю силовської комутативності.